2013
DOI: 10.1111/jgs.12225
|View full text |Cite
|
Sign up to set email alerts
|

Tooth Loss and Mortality in Elderly Japanese Adults: Effect of Oral Care

Abstract: Tooth brushing, regular dental visits, and use of dentures are inversely associated with mortality in elderly individuals with tooth loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
72
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 30 publications
(68 reference statements)
5
72
0
Order By: Relevance
“…In a study of 21,700 elderly Japanese, tooth brushing and regular dental visits were associated with survival after controlling for age, sex, education level, smoking, drinking, and medical history. 26 Other studies have found an association between tooth loss and overall mortality in Danish, 27 Taiwanese, 28 Scottish, 29 French 30 and Chinese populations. 31 The mechanism is unclear and it has been suggested that markers of oral health such as tooth loss, visits to the dentist, and tooth brushing may serve as a proxy for life and health stressors that can affect mortality.…”
Section: Discussionmentioning
confidence: 96%
“…In a study of 21,700 elderly Japanese, tooth brushing and regular dental visits were associated with survival after controlling for age, sex, education level, smoking, drinking, and medical history. 26 Other studies have found an association between tooth loss and overall mortality in Danish, 27 Taiwanese, 28 Scottish, 29 French 30 and Chinese populations. 31 The mechanism is unclear and it has been suggested that markers of oral health such as tooth loss, visits to the dentist, and tooth brushing may serve as a proxy for life and health stressors that can affect mortality.…”
Section: Discussionmentioning
confidence: 96%
“…Paganini-Hill et al (9) followed 5,611 men and women for 17 years in the United States and reported that people with poor oral hygiene habits had a higher risk of mortality (9). A study on 21,730 community residents in Japan also reported that people with poor oral health care habits had a higher risk of mortality (10).…”
Section: Introductionmentioning
confidence: 96%
“…Many studies of oral health status have examined factors such as number of teeth, oral hygiene, denture use status, saliva secretion, and masticatory function to clarify any relationship with mortality in the elderly [17]. In addition, masticatory function has been studied in terms of nutritional analysis from the diet, functional analysis by muscle activity involved in chewing, and analysis of the maximum occlusal force (MOF) [810].…”
Section: Introductionmentioning
confidence: 99%